Bibliometric Analysis: Debt Literacy for Reducing Over-Debt and Poverty Alleviation - Nur Hidayat; Hikmatul Hasanah (Universitas Gorontalo, 2022)
After the 2008 financial crisis, research on topics related to debt literacy gradually intensified. However, there were only 251 articles that looked at debt literacy between 1985 to 2020. Scholars' interest in identifying the cause of the Lehman Brothers collapse has skyrocketed since it happened. The biggest contributing factor is allegedly a lack of financial knowledge. The dimensions relating to debt literacy can be solved and mapped using this bibliometric methodology. Using Vos-viewer software and publish or perish can assist determine it. The Ministry of Foreign Affairs Publication Background Notes Series has nine publications, and the International Journal of Consumer Studies has eight. These two publications account for the majority of all publications. Cwynar, Gathergood, and Lusardi are three researchers who are involved in and concerned about the subject of debt literacy. With 97 publications, the United States is the largest publishing nation overall. Gender, adulthood, household finances, financial management, financial knowledge, financial aptitude, and excessive debt are all relevant topics for future research in the area of debt literacy.